A Typology Study And Factors Affecting Land Conversion In Dukuhwaluh Village, Kembaran Sub-District, Banyumas - Ayundasari, Cantika Diffa; Suwarsito, Suwarsito; Sarjanti, Esti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aimed to determine the number of land conversions, the factors affecting landconversion, and the typology of land conversion. This is a descriptive study applying fieldresearch that aimed at obtaining primary and secondary data. The population covered 12people owner of agricultural land. This sampling technique employed the snowball method.The data required were primary and secondary data. Data analysis used descriptivequalitative to describe the analysis of land conversion, the factors affecting it, and thetypology of land conversion. The results revealed that there was a change in landconversion in Dukuhwaluh Village of 26,094 Ha or 14,235%. The most dominant landconversion was residential land which increased to 12,518 Ha, and mixed garden land wasreduced to 3,985 Ha, and irrigated paddy land was reduced to 9,062 Ha. There were 2factors affecting land conversion; internal and external factors. Internal factors were thecommunity did not rely on agricultural land as a source of income, agricultural productsmet the needs of life, the landowners decided to convert his land because of his owndecision. External factors were the foundation offered high prices to buyers. The typologywas patterned systematic conversion, land conversion in response to population growth,multi-form or amorphous conversion.